Relationship between the TLR5 -1174C>T Polymorphism in Patients with peptic ulcer and Helicobacter pylori infection in Mazandaran province - Morteza Tajdar; Rasool Zahmatkesh Roodsari (مجله دانشگاه علوم پزشکی بیرجند)
Background and Aims: Peptic ulcer is a painful inflammatory disease occurring inside the gastric or the first part of the small intestine (duodenum). One of the leading causes of this disease is Helicobacter pylori infection. Toll-like receptors (TLRs) play a crucial role as a warning factor in the detection of Helicobacter pylori infection in the immune system. TLRs belong to a group of pattern recognition receptors of the host's innate immune system. The present study aimed to assess the relationship between the C1174T polymorphism of the TLR5 gene and Helicobacter pylori infection in patients with peptic ulcers in Mazandaran province. Materials and Methods: This case-control study investigated 150 patients with peptic ulcer and Helicobacter pylori infection and 150 healthy individuals. After extracting genomic DNA from gastric biopsy samples, genotypic and allelic frequency in patients and control group was determined by Three primer ARMS PCR method. Data were analyzed in SPSS software (version 23). Results: The frequency rates of CC, CT, and TT genotypes in patients were 19.3%, 49.3%, and 31.3%, respectively. In healthy people, these values were obtained at 38.6%, 45.3%, and 16%, respectively. Statistical analysis demonstrated a significant relationship between the C1174T polymorphism of the TLR5 gene and peptic ulcer disease. Conclusion: As evidenced by the results of this study, the presence of the T allele at the C1174T position can be considered a factor for increasing the risk of peptic ulcer disease; nonetheless, the investigation of other TLR5 gene polymorphisms in larger populations is needed.